2017
DOI: 10.1111/os.12341
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential Reconstruction of Subaxial Cervical and Cervicothoracic Spine by Simultaneously Combined Anterior–posterior Approaches in the Sitting Position

Abstract: The "sitting position" simultaneously combined anterior-posterior approach is safe and is superior to the traditional prone position and supine position, and the surgical results are satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…1 Reports have also indicated that sitting procedures allow for the maintenance of a more normal anatomical alignment of the cervical spine and used the 360° of access afforded by the sitting position in order to perform frontback procedures. 14,19 We also noted reduced episodes of hypoventilation postoperatively in sitting cases, which logically follows compared to the challenges with ventilation in the prone position and may merit consideration in patients in whom adequate ventilation is a particular concern.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…1 Reports have also indicated that sitting procedures allow for the maintenance of a more normal anatomical alignment of the cervical spine and used the 360° of access afforded by the sitting position in order to perform frontback procedures. 14,19 We also noted reduced episodes of hypoventilation postoperatively in sitting cases, which logically follows compared to the challenges with ventilation in the prone position and may merit consideration in patients in whom adequate ventilation is a particular concern.…”
Section: Discussionmentioning
confidence: 62%
“…Much of the research on the sitting position in neurosurgery has focused on posterior fossa cranial surgeries or deep brain stimulation, though we have also recently reported on a large cohort that included cervical procedures performed in patients in the sitting position. 19 However, few reports are specifically dedicated to posterior cervical procedures or provided a direct comparison of sitting and prone procedures. Several recent publications have discussed minimally invasive approaches to the posterior cervical spine with patients in the sitting position, and one recent series even made use of instrumented procedures, demonstrating ongoing interest in its use.…”
Section: Discussionmentioning
confidence: 99%
“…Комбіновані хірургічні підходи представлені передньо-задніми, задньо-передніми, у деяких випадках -задньо-передньо-задніми або передньо-задньо-пере дніми. Основною перевагою комбінованої 360°-стабілізації є надійна фіксація прооперованого ХРС, що дає змогу значно обмежити залишковий обсяг рухів [77,78]. Відзначено, що комбінована стабілізація при вивихах/переломо-вивихах ШВХ на субаксіальном рівні збільшує швидкість консолідації, однак не має значущих переваг щодо регресу неврологічних порушень [79].…”
Section: комбіновані доступиunclassified